Penggunaan Metode Pembelajaran Kooperatif Tipe Think Pair Share Untuk Meningkatkan Hasil Belajar Siswa Kelas XI Pada Mata Pelajaran Geografi - Jubaeda Umar; Syahril Lukman (Jurnal Ilmiah Wahana Pendidikan, 2022)
Teachers as spearheads and drivers of educational progress are expected to be able to provide an effective learning atmosphere by choosing the right learning methods so that students can achieve good learning outcomes. The learning method that is considered appropriate to improve student learning outcomes on flora and fauna material in Indonesia and the world is the think pair share learning method. This study aims to determine the implementation of the TPS (Think-Pair-Share) method is able to improve the learning outcomes of Geography. The type of research used is Classroom Action Research (CAR). The subjects of this study were 25 students of class XI SMA Negeri 6 Ternate City. The results obtained in the first cycle are 76% classical learning completeness or 19 students have met the KKM and the average student score is 74.2, with the highest student score 80 and the lowest 50. While in the second cycle classical learning completeness increased to 92% or 23 students who have reached the KKM of a total of 25 students and the average value of students is 82.6, with the highest score of 90 and the lowest 60. Based on the results of this study, thus the application of think pair share cooperative learning method can improve student learning outcomes class XI in geography.